1992
DOI: 10.1136/ard.51.8.932
|View full text |Cite
|
Sign up to set email alerts
|

A 12 year follow up study in the general population on prognostic factors of cartilage loss in osteoarthritis of the knee.

Abstract: The natural history and prognostic factors of cartilage loss in osteoarthritis of the knee were studied in subjects from a general population survey on rheumatic diseases in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
165
3
8

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 266 publications
(189 citation statements)
references
References 22 publications
(6 reference statements)
10
165
3
8
Order By: Relevance
“…The clinical diagnosis of local OA made by a physical examination was not related to radiologic progression of knee OA in the study by Schouten et al (37).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…The clinical diagnosis of local OA made by a physical examination was not related to radiologic progression of knee OA in the study by Schouten et al (37).…”
Section: Resultsmentioning
confidence: 82%
“…No significant association was found between current use, past use, or never use of estrogen and progression of knee OA. Schouten et al (37) found no association between uric acid concentration and progression of knee OA.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations